Teaching practices of Arabic Language teachers in Developing Reading Skills Among Middle School Students (Journal of the College of Basic Education, 2026)
This study aimed to determine the level of teaching practices of Arabic language teachers in developing reading skills among middle school students, and to reveal the extent of differences in the average responses of the study sample members attributable to differences in qualifications, teaching experience, and training courses. The descriptive approach was used on a sample of (48) Arabic language teachers in government middle schools in Samtah Governorate. The study instrument was an observation checklist in its final form, consisting of (18) statements distributed across six axes: pronunciation skills, direct comprehension skills, critical comprehension skills, analytical skills, inferential comprehension skills, and creative comprehension skills. The results showed that the overall mean of Arabic language teachers' practice of pronunciation skills among middle school students was moderate, reaching (2.30) with a standard deviation of (0.31367). The overall mean of Arabic language teachers' practice of direct comprehension skills among middle school students was also moderate, reaching (2.29) with a standard deviation of (0.32687). However, the overall mean of Arabic language teachers' practice of critical comprehension skills among middle school students was high. The overall mean of Arabic language teachers' practice of analytical skills among middle school students was (2.26) with a standard deviation of (0.50912), and the overall mean of their practice of deductive reasoning skills was (2.21) with a standard deviation of (0.28391). The overall mean of their practice of creative reasoning skills was (2.23) with a standard deviation of (0.30910). The results also showed statistically significant differences at the (α≤0.05) level based on the variables of qualification, years of experience, and training courses. In light of these results, the study recommends increasing training courses in reading skills for Arabic language teachers, integrating reading skills into teaching plans, training teachers, utilizing these skills in curricula, and intensifying specialized training programs focused on developing reading skills.